Kahoot, is it fun or unfun? Gamifying vocabulary learning to boost exam scores, engagement, and motivation - Rojabi, Ahmad Ridho; Setiawan, Slamet; Munir, Ahmad; Purwati, Oikurema; Safriyani, Rizka; Hayuningtyas, Nina; Khodijah, Siti; Amumpuni, Rengganis Siwi (Frontiers in Education, 2022)
In language learning environments, technology is rapidly manipulated to encourage engagement, promote autonomy, and boost motivation. Many instructors have initiated to exploit online platforms and tools as a more engaging alternative to conventional activities. One of the engaging, and enjoyable games is Kahoot. The purpose of this study is to perceive the course content of Kahoot in the classroom to increase exam scores in vocabulary, and boost student engagement, and motivation. In addition, this study also explored the issues encountered by students in vocabulary learning through Kahoot. The impact of gamification on student achievement was assessed using quantitative and qualitative methods on the first-year students of the English department (N=82). The findings revealed that incorporating Kahoot for teaching vocabulary effectively allows learners to expand a deeper understanding of vocabulary and course concepts indicated by exam scores improvement. This method also has a positive impact on student engagement as well as motivation. Furthermore, rigorous future research is needed to fully understand Kahoot’s efficacy and to improve pedagogy in the vocabulary classroom.